IMPLEMENTASI METODE DEMOSTRASI UNTUK MENINGKATKAN HASIL BELAJAR SISWA MATA PELAJARAN FIKIH MATERI SHOLAT DI SMPN 13 MALANG - Linda Puspitasari; Ika Ratih Sulistiani; Bahroin Budiya (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
Education is the most important thing in improving the quality of human resources, learning goes well if the teacher better understands the condition of students, one of which is the psychological factor, namely a sense of self-esteem. The purpose of this study was to determine the implementation of the demonstration method to improve student learning outcomes in fiqh subjects, prayer materials at SMP 13 Malang, East Java, and to determine student learning outcomes using the demonstration method. Types The types used in this research are classroom action research or CAR. The researcher took direct sources from class VIII A students and teachers who teach Fiqh at SMPN 13 Malang, East Java. In this case the researcher in determining the sample uses the Purpose Sampling technique. The results showed that there was an increase in learning outcomes from pre-cycle with students who completed 50%, to cycle I students who completed 70% and cycle II students who completed 90%. This means that the demonstration method is able to improve student learning outcomes.Kata Kunci: Pendidikan, Metode Demostrasi, PTK